2018
DOI: 10.3390/w10111589
|View full text |Cite
|
Sign up to set email alerts
|

Soil Salinity Assessment Using Saturated Paste and Mass Soil:Water 1:1 and 1:5 Ratios Extracts

Abstract: Soil salinization is directly related to the quantity and quality of food production, and often, to increased energy demands for high-quality irrigation water. Reliable monitoring of soil salinity based on a less laborious method than the soil saturated paste (SP) extract methodology is required. In the present study, an attempt is made to relate the electrical conductivity (EC) of the soil saturated paste (SP) extract (ECe) with the EC determined in the 1:1 and 1:5 soil over water mass ratios, (soil:water) ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 17 publications
(64 reference statements)
6
34
0
1
Order By: Relevance
“…These data confirm the existence of a strong linear relationship when the range of EC e is relatively great ( Table 1). As shown in Table 4, the relationship EC e = fEC 1:5 using the USDA method is similar to the corresponding one reported by Kargas et al [7], (Table 1) for Greek soils since both the two equations have almost the same slope (6.61 and 6.53, respectively).…”
Section: Relationship Between Ec E and 1:5 Soil To Water Extract Elecsupporting
confidence: 86%
“…These data confirm the existence of a strong linear relationship when the range of EC e is relatively great ( Table 1). As shown in Table 4, the relationship EC e = fEC 1:5 using the USDA method is similar to the corresponding one reported by Kargas et al [7], (Table 1) for Greek soils since both the two equations have almost the same slope (6.61 and 6.53, respectively).…”
Section: Relationship Between Ec E and 1:5 Soil To Water Extract Elecsupporting
confidence: 86%
“…Other researchers have reported that the coefficient value of regression models varies according to the differences in soil characteristics (soil texture, clay type, solutes types, and organic matter) (Al‐Mustafa & Al‐Omran, 1990; Chi & Wang, 2010; He et al, 2013; Khorsandi & Yazdi, 2007; Shaw, 1994; Slavich & Petterson, 1993; Sonmez et al, 2008). However, the observed result variations among various studies could be most likely attributed to the different methodologies used for EC 1:5 determination (Kargas et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The regression coefficients (slope) in this study were different from reported values of some studies (Chi & Wang, 2010; Loveday, Beatty, & Norris, 1972; Sonmez et al, 2008). Regression coefficients range has been reported from 6 to 11 (Chi & Wang, 2010; Kargas et al, 2018; Loveday et al, 1972), 7.36 to 8.22 (Sonmez et al, 2008), 6.9 to 5.4 (Khorsandi & Yazdi, 2007, 2011), 5.04 (Aboukila & Norton, 2017), and 7.46 (Aboukila & Abdelaty, 2017). Nevertheless, the values in other studies are much greater than the obtained values in the current study (0.44–0.66).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil textures were predominantly silty clay having clay fraction of 45%-50% and silt fraction of 41%-46%. Soil electrical conductivity (EC) was measured using soil saturated paste extract methodology and it was ranged from 0.68 dS/m to 0.98 dS/m [48] . The values of EC greater than 4 dS/m indicated the salinity problems [49] .…”
Section: Resultsmentioning
confidence: 99%